1990
DOI: 10.1164/ajrccm/141.5_pt_1.1158
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Radicals Produce Airway Constriction and Hyperresponsiveness in Anesthetized Cats

Abstract: Using 30 anesthetized cats, we examined whether oxygen radicals produce airway constriction or hyperresponsiveness. In one group, we administered aerosolized xanthine (0.1%) for 3 min followed by aerosolized xanthine oxidase (XO) (1 U/ml) for 5 min in order to generate oxygen radicals enzymatically in the airways. Pulmonary resistance (RL) instantaneously increased from 14.8 +/- 0.9 to 30.8 +/- 1.4 cm H2O/L/s (p less than 0.01). The increase in RL was significantly depressed by prior administration of polyethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 0 publications
0
56
0
4
Order By: Relevance
“…These studies have demonstrated the increase in inflammatory cells such as neutrophils and eosinophils associat-ed with the development of airway hyperresponsiveness (Holtzman et al 1983;Murphy et al 1986;Gundel et al 1990). Inflammatory cells produce oxygenderived free radicals which have been suggested to be related to the development of bronchial hyperreactivity (Katsumata et al 1990) and inactivation of proteolytic enzyme by oxidation (Dusser et al 1989). Thus, the inactivation of enzymes by the inflammation may provide a new mechanism of bronchial hyperresponsiveness in bronchial asthma.…”
Section: Mucus In the Peripheral Airwaymentioning
confidence: 99%
“…These studies have demonstrated the increase in inflammatory cells such as neutrophils and eosinophils associat-ed with the development of airway hyperresponsiveness (Holtzman et al 1983;Murphy et al 1986;Gundel et al 1990). Inflammatory cells produce oxygenderived free radicals which have been suggested to be related to the development of bronchial hyperreactivity (Katsumata et al 1990) and inactivation of proteolytic enzyme by oxidation (Dusser et al 1989). Thus, the inactivation of enzymes by the inflammation may provide a new mechanism of bronchial hyperresponsiveness in bronchial asthma.…”
Section: Mucus In the Peripheral Airwaymentioning
confidence: 99%
“…The activation of recruited neutrophils by locally generated mediators, including formyl peptides produced by proliferating bacteria [2] and eukaryotic mitochondria [3], leads to the release of histotoxic compounds such as enzymes and oxidants [4]. Other than causing tissue injury, neutrophil oxidants are presently thought to be involved in the pathogenesis of airway hyperreactivity and/ or bronchoconstriction [5,6]. As in other neutrophilic inflammatory processes, the extent of the neutrophil activation and, in turn, the generation of oxidants are down-regulated by endogenous mediators, mainly circulating catecholamines [7,8] and locally produced prostaglandins such as PGE 2 [9], via augmentation of intracellular levels of cyclic AMP (cAMP).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS generation is found when the activity of neutrophils, eosinophils, monocytes and macrophages is increased, as occurs in asthma (Kelly et al, 1988). Oxidative stress (a situation of imbalance between the production of ROS and the ability to detoxify the reactive intermediates or to repair the resulting damage) is an important consequence of asthma inflammation; is associated with an altered activity in anti-oxidation in lungs and blood; and also with airway reactivity (Katsumata et al, 1990;Nadeem et al, 2005;Sackesen et al, 2008). There are numerous reports showing deficiencies of antioxidants in asthma: low levels of vitamin C in airway lining fluid, serum, plasma, whole blood and brochoalveolar lavage fluid; vitamin E in brochio-alveolar lavage fluid, red cells and plasma; or beta-carotene in serum (Kalayci et al, 2000;Kelly et al, 1999;Sackesen et al, 2008;Shanmugasundaram et al, 2001;Vural & Uzun, 2000;Wood et al, 2008).…”
Section: Diet As An Independent Factor In the Development Of Asthma Amentioning
confidence: 99%